Modernization of Javanese Personal Names in Kelurahan Tanjung Mulia - Rizky Vita Losi; Busmin Gurning (LINGUISTIK TERAPAN, 2016)
This research dealt with the Javanese personal names in Kelurahan Tanjung Mulia. The objectives of this descriptive qualitative study were (1) to determine the sources of name of Javanese personal names, (2) to describe the forms of modern names, and (3) to explain the reasons of name choice that the Javanese parents chose their children’s name as the way they did. The data were obtained from Javanese children’s personal names and Javanese parents’ interview result. The data were identified, analyzed and categorized based on (Rasekh, 2012), (Sahid, 2013) and (Virkkula, 2014) theories. The findings of the study showed that: (1) there were thirteen sources of name were found in Kelurahan Tanjung Mulia, Medan namely names of motherland, personal features, occupations, the time of birth, objects around, traditions or local customs, variations of another name, geographical places, names of important people, names ofancestors, names based on nature, harmonyof names, and innovation names, (2) three forms of modern name were found as well in Kelurahan Tanjung Mulia, namely names with a Javanese influence, the use of western name elements and names with an Islamic influence, (3) the reasons of name choice were found as tradition and family, international names, aesthetic values and positive meanings, current names and parents’ name identity. Keywords: personal names, source of names, form of modern names, name choice